RITUXIMAB EFFICACY IN TREATING SYSTEMIC JUVENILE ARTHRITIS REFRACTORY TO TRADITIONAL IMMUNOSUPPRESSANT AND TNF BLOCKER THERAPY - E.I. Alexeeva; S.S. Akulova; E.L. Semikina; T.M. Bzarova; K.B. Isaeva ("Paediatrician" Publishers LLC, 2007)
The article describes the clinical case of a difficult systemic juvenile arthritis refractory to traditional immunosuppressant and TNF blocker therapy. The disease was characterized by such extra-articulate manifestations as fever, lymphadenopathy, hepatolienomegaly, polyorrhymenitis, generalized joint affection and high laboratory activity indicators (ESR, CRP). The inclusion of rituximab stimulated the remission of systemic manifestations and the joint syndrome, as well as normalized the laboratory disease activity indicators. The therapeutic effect duration was 22 weeks upon the initial infusion of rituximab. The results demonstrate that rituximab is a promising medication for treating systemic juvenile arthritis children. Key words: children, treatment, rituximab, juvenile arthritis.